A common trinucleotide repeat expansion within the transcription factor 4 (TCF4, E2-2) gene predicts Fuchs corneal dystrophy. - Eric D Wieben; Ross A Aleff; Nirubol Tosakulwong; Malinda L Butz; W Edward Highsmith; Albert O Edwards; Keith H Baratz (PLoS ONE, 2012)
Fuchs endothelial corneal dystrophy (FECD) is a common, familial disease of the corneal endothelium and is the leading indication for corneal transplantation. Variation in the transcription factor 4 (TCF4) gene has been identified as a major contributor to the disease. We tested for an association between an intronic TGC trinucleotide repeat in TCF4 and FECD by determining repeat length in 66 affected participants with severe FECD and 63 participants with normal corneas in a 3-stage discovery/replication/validation study. PCR primers flanking the TGC repeat were used to amplify leukocyte-derived genomic DNA. Repeat length was determined by direct sequencing, short tandem repeat (STR) assay and Southern blotting. Genomic Southern blots were used to evaluate samples for which only a single allele was identified by STR analysis. Compiling data for 3 arms of the study, a TGC repeat length >50 was present in 79% of FECD cases and in 3% of normal controls cases (p<0.001). Among cases, 52 of 66 (79%) subjects had >50 TGC repeats, 13 (20%) had <40 repeats and 1 (2%) had an intermediate repeat length. In comparison, only 2 of 63 (3%) unaffected control subjects had >50 repeats, 60 (95%) had <40 repeats and 1 (2%) had an intermediate repeat length. The repeat length was greater than 1000 in 4 FECD cases. The sensitivity and specificity of >50 TGC repeats identifying FECD in this patient cohort was 79% and 96%, respectively Expanded TGC repeat was more specific for FECD cases than the previously identified, highly associated, single nucleotide polymorphism, rs613872 (specificity = 79%). The TGC trinucleotide repeat expansion in TCF4 is strongly associated with FECD, and a repeat length >50 is highly specific for the disease This association suggests that trinucleotide expansion may play a pathogenic role in the majority of FECD cases and is a predictor of disease risk.